Experiences in development of DOR Bt-1 technology: the highs and lows during the sojourn: EXPERIENCES IN DEVELOPMENT OF DOR BT-1 TECHNOLOGY: THE HIGHS AND LOWS DURING SOJOURN - P S VIMALA DEVI (Journal of Oilseeds Research, 2020)
Insect pest management is important to save the crop from yield losses and increase productivity. In India, about 33% of the crop loss occurs due to insect pests and is worth of about ` 200 thousand crores annually. In addition substantial volume of agricultural exports is rejected every year due to pesticide residues. The pesticides are unsafe for environment and human health; their misuse by farmers further aggravates the problem. Therefore, sustainable and eco-friendly pest management practices are needed. In this article, I share my personal experiences during the two-decade sojourn, marked by struggles and breakthroughs, which culminated in a successfully commercialized biocontrol technology that has reached the farmers.